Emergency Laparoscopic Repair of an Iatrogenic Gastric Perforation in a Hiatal Hernia following a Failed Endoscopic Closure. (25th March 2020) - Reed, Benjamin L.; Tabone, Lawrence E.; Szoka, Nova; Abunnaja, Salim
Abstract : Iatrogenic gastrointestinal perforation is a rare, life-threatening complication of endoscopic procedures, which requires either endoscopic or surgical repair. We report the account of an 82-year-old woman with an iatrogenic gastric perforation of a hiatal hernia secondary to an endoscopic retrograde cholangiopancreatography (ERCP) procedure. Despite immediate recognition of the complication and endoscopic closure with through-the-scope (TTS) clips, the patient developed mediastinitis, peritonitis, and sepsis. She subsequently underwent an emergency laparoscopic hiatal hernia dissection and repair of the perforation with mediastinal and peritoneal washout. Given the patient's age and the degree of insult, subdiaphragmatic anchoring with abdominal drain placement was performed, and the hiatus was left open for additional drainage. The use of a side-viewing duodenoscope with the presence of a large hiatal hernia contributed to the risk of gastric perforation. We conclude that performing endoscopic procedures in patients with a known hiatal hernia should be carefully undertaken. If a perforation in such patients occurs, laparoscopic repair of such complications is feasible as demonstrated in this case video.